An economic evaluation of knee osteoarthritis treatments in Thailand - Luksameesate, Parnnaphat; Tanavalee, Aree; Taychakhoonavudh, Suthira (Frontiers in Pharmacology, 2022)
Objective The objective of this study is to evaluate the cost-effectiveness of different knee OA care sequences compared to standard treatment reimbursed by the major health insurance payer in Thailand. Method We used decision analytical modeling to evaluate the effect of either adding etoricoxib or crystalline glucosamine sulfate compared to standard treatment from a societal perspective over patients' lifetimes. Data was analyzed based on efficacy while adverse events were considered as sub-state. Model input data was retrieved from relevant published literature and the Standard Cost Lists for Health Technology Assessment, Thailand. All health outcomes were measured in a unit of quality-adjusted life-year (QALY). An incremental cost-effectiveness ratio (ICER) was applied to examine the costs and QALYs. Sensitivity analysis was performed to investigate the robustness of the model. Result The results demonstrated that adding crystalline glucosamine sulfate (before diclofenac plus proton pump inhibitors, PPI) into the standard care sequence was a dominant strategy compared to the standard care sequence. Adding etoricoxib alone or including crystalline glucosamine sulfate (after diclofenac plus PPI) was dominated by adding crystalline glucosamine sulfate (before diclofenac plus PPI). Whereas a willingness-to-pay (WTP) threshold in Thailand, adding of both crystalline glucosamine sulfate (before diclofenac plus PPI) and etoricoxib were cost-effective when compared to adding crystalline glucosamine sulfate alone with ICER of 125,547 Thai baht/QALY (3,472 US dollars/QALY). Conclusion The addition of crystalline glucosamine sulfate and etoricoxib into standard knee OA treatment were cost-effective at the WTP threshold in Thailand. Additionally, early initiation of crystalline glucosamine sulfate would be less costly and more effective than delayed treatment or the use of standard treatment alone.